2018
DOI: 10.1146/annurev-med-051215-030943
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Approaches for Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a common genetic condition characterized by elevated plasma levels of low-density lipoprotein cholesterol (LDL-C), premature atherosclerotic cardiovascular disease, and considerable unmet medical need with conventional LDL-C-lowering therapies. Between 2012 and 2015, the US Food and Drug Administration approved four novel LDL-C-lowering agents for use in patients with FH based on the pronounced LDL-C-lowering efficacy of these medicines. We review the four novel approved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 90 publications
1
16
0
Order By: Relevance
“…However, both agents may cause liver steatosis and are currently only in use as adjunct therapy in homozygous familial hypercholesterolemia 31,[238][239][240][241] . No data are available on cardiovascular outcomes with either lomitapide or mipomersen 242,243 .…”
Section: [H2] Inhibitors Of Vldl Productionmentioning
confidence: 99%
“…However, both agents may cause liver steatosis and are currently only in use as adjunct therapy in homozygous familial hypercholesterolemia 31,[238][239][240][241] . No data are available on cardiovascular outcomes with either lomitapide or mipomersen 242,243 .…”
Section: [H2] Inhibitors Of Vldl Productionmentioning
confidence: 99%
“…Nonetheless, it is clear already that lncRNAs will emerge as important new therapeutic targets for the treatment of metabolic disorders, including dyslipidemias, hepatosteatosis and atherosclerosis. ASO-based therapies to inhibit mRNAs and lncRNAs are actively being pursued, with mipomersen, the apoB-targeting ASO for treatment of familial hypercholesterolemia leading the way with FDA-approval [63,64]. As the mysteries of lncRNAs continue to be unraveled, parallel improvements of therapeutic tools to target non-coding RNAs in tissue-specific ways will no doubt accelerate the development future RNA-based therapies for diseases in the area of lipid metabolism and beyond.…”
Section: Resultsmentioning
confidence: 99%
“…The most common adverse effects of mipomersen, when used continuously for 2 years, are injection-site reactions (98% of patients), flu-like symptoms (65%), and clinically relevant elevations of liver enzymes (13%) 59 . Most studies have also documented significant increases in hepatic fat content (in line with the drugÂŽs mechanism -inhibition of lipoprotein production and secretion by the liver) 3,57,58 . A study of liver biopsies from patients chronically treated with mipomersen showed severe steatosis in most patients (five out of seven), albeit without histological signs of nonalcoholic steatohepatitis.…”
Section: Mipomersenmentioning
confidence: 94%
“…Despite the widespread use of efficacious lipid-modifying therapies, the residual risk of CVD remains unacceptably high 1 . Besides suboptimal control of non-lipid risk factors, our ability to reduce CVD is also constrained by intolerance or poor adherence to statin therapy 2 , limited availability and access to therapies for severe, genetic dyslipidemias 3 , and inconsistent evidence about the benefits of impacting the high-density lipoprotein (HDL)/triglycerides (TG) axis 4 .…”
Section: Introductionmentioning
confidence: 99%